2016
DOI: 10.1155/2016/2987472
|View full text |Cite
|
Sign up to set email alerts
|

Early Sexual Debut and HIV Infection among Men Who Have Sex with Men in Shenzhen, China

Abstract: Studies investigating the association between early sexual debut and human immunodeficiency virus (HIV) infection have mainly focused on Africans or females but rarely on men who have sex with men (MSM) in China. This study, therefore, mainly aimed at exploring the association between early sexual debut and HIV infection among MSM in Shenzhen, China. A total of 533 MSM were enrolled in this study using a convenience sampling method. Information about sociodemographic characteristics and risky sexual behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
2
12
0
3
Order By: Relevance
“…However, few studies have comparable results. Researches concerning same-sex behavior focused mainly on age and HIV risk [ 39 42 ], while others found that older MSM reported less MSM behaviors [ 32 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have comparable results. Researches concerning same-sex behavior focused mainly on age and HIV risk [ 39 42 ], while others found that older MSM reported less MSM behaviors [ 32 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anal sex roles also contribute to high risk of HIV seroconversion especially among YMSM who adopt the receptive anal sex role without a condom [5, 25]. Early age at first anal sex has been shown to be associated with HIV acquisition among MSM; studies also demonstrate early age at first anal sex is associated with sexual risk taking [26, 27]. Published literature has shown that the trend of HIV infection has continued to increase, with potential risk factors including age structure, sexual behavior and relationships, STIs, substance use, and virtual and physical venues contributing to the HIV epidemic in YMSM.…”
Section: Introductionmentioning
confidence: 99%
“…Early sexual debut could be a risk factor for STIs including HIV/AIDS among sexual minority groups 16. Our study identified a positive association between identifying with a minority sexual orientation and having an earlier sexual debut.…”
Section: Discussionmentioning
confidence: 49%